2009
DOI: 10.1002/nme.2777
|View full text |Cite
|
Sign up to set email alerts
|

Topology optimization for stationary fluid–structure interaction problems using a new monolithic formulation

Abstract: SUMMARYThis paper outlines a new procedure for topology optimization in the steady-state fluid-structure interaction (FSI) problem. A review of current topology optimization methods highlights the difficulties in alternating between the two distinct sets of governing equations for fluid and structure dynamics (hereafter, the fluid and structural equations, respectively) and in imposing coupling boundary conditions between the separated fluid and solid domains. To overcome these difficulties, we propose an alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
96
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(97 citation statements)
references
References 44 publications
(85 reference statements)
1
96
0
Order By: Relevance
“…These works showed that pressure loading problems can be efficiently solved with density-based topology optimization by using different pressure boundaries modeling techniques. The idea of using mixed element formulations by Sigmund and Clausen (2007) could be further applied in a range of different multiphysics problems (Yoon, Jensen and Sigmund 2007;Yoon and Sigmund 2008;Yoon 2010).…”
Section: Catenary Risermentioning
confidence: 99%
“…These works showed that pressure loading problems can be efficiently solved with density-based topology optimization by using different pressure boundaries modeling techniques. The idea of using mixed element formulations by Sigmund and Clausen (2007) could be further applied in a range of different multiphysics problems (Yoon, Jensen and Sigmund 2007;Yoon and Sigmund 2008;Yoon 2010).…”
Section: Catenary Risermentioning
confidence: 99%
“…heat (Yoon, 2010a;Marck et al, 2013;Alexandersen et al, 2016). Models for including the fluid structure interaction have been developed as demonstrated in Yoon (2010b) and Kreissl et al (2010). In this work, the deformations of the component are assumed negligible, and thus the solid is assumed infinitely stiff and no interaction is modeled.…”
Section: Primary Inflow Outflowmentioning
confidence: 99%
“…The application of topology optimization to fluid structure interaction problems has only recently been approached. Yoon (2010) presented a method for converting the interface stresses to a volume integral which is suited for a monolithic formulation. Kreissl et al (2010) presented a one way coupling used for the design of flexible micro-fluidic devices.…”
Section: Introductionmentioning
confidence: 99%